2020
DOI: 10.1103/physrevc.101.034303
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the symmetry energy and its associated parameters from nuclei to neutron stars

Abstract: The symmetry energy obtained with the effective Skyrme energy density functional is related to the values of isoscalar effective mass and isovector effective mass, which is also indirectly related to the incompressibility of symmetric nuclear matter. In this work, we analyze the values of symmetry energy and its related nuclear matter parameters in five-dimensional parameter space by describing the heavy ion collision data, such as isospin diffusion data at 35 MeV/u and 50 MeV/u, neutron skin of 208 Pb, and ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 102 publications
(154 reference statements)
10
53
0
Order By: Relevance
“…Various studies have empirically identified correlations between various combinations of parameters that characterize the symmetry energy and its density dependence with the neutron star radius and tidal parameters [246,[266][267][268][269] or terrestrial experimental results [239,[270][271][272], as they all are linked to the low-density behavior of the equation of state around (twice) saturation. The tidal constraints from GW170817, and more recently radius constraints from NICER have been used to examine implications for the symmetry energy [273][274][275][276][277][278][279][280][281][282] as well as potential systematics in the mapping [283].…”
Section: Microscopic Propertiesmentioning
confidence: 99%
“…Various studies have empirically identified correlations between various combinations of parameters that characterize the symmetry energy and its density dependence with the neutron star radius and tidal parameters [246,[266][267][268][269] or terrestrial experimental results [239,[270][271][272], as they all are linked to the low-density behavior of the equation of state around (twice) saturation. The tidal constraints from GW170817, and more recently radius constraints from NICER have been used to examine implications for the symmetry energy [273][274][275][276][277][278][279][280][281][282] as well as potential systematics in the mapping [283].…”
Section: Microscopic Propertiesmentioning
confidence: 99%
“…[122], while the correlation between the maximum mass M max and Λ 1.4 found in Ref. [89] is not observed due to the first-order deconfinement phase transition.…”
Section: Resultsmentioning
confidence: 75%
“…The corresponding EOSs for hybrid star matter are obtained, which predict the structures of compact stars by solving the TOV equation. It is found that the correlation between radius and tidal deformability in traditional neutron stars [89,122] preserves in hybrid stars. Once quark matter emerges inside compact stars, the quark-hadron interface plays an important role on their structures.…”
Section: Discussionmentioning
confidence: 98%
“…Several attempts have been taken to explore this object [40,89]. Some of the suggestions are as follows: (i) It is a heavy NS with deconfined QCD core [90], (ii) a super-fast pulsar [91], (iii) a binary black-hole merger [28,92] and (iv) the DM admixed NS with EOS is sufficiently stiff [40] etc. If this event is the merger of the NS and black hole (NSBH), then the tidal deformability of the NS for the canonical star is Λ 1.4 = 616 +273 −158 .…”
Section: Electric Love Number and Tidal Deformabilitymentioning
confidence: 99%